Prenylated Stilbenoids Affect Inflammation by Inhibiting the NF-κB/AP-1 Signaling Pathway and Cyclooxygenases and Lipoxygenase - Hošek, Jan; Leláková, Veronika; Bobál, Pavel; Pížová, Hana; Gazdová, Markéta; Malaník, Milan; Jakubczyk, Karolina; Veselý, Ondřej; Landa, Přemysl; Temml, Veronika; Schuster, Daniela; Prachyawarakorn, Vilailak; et al. (Journal of natural products, 2019)
Stilbenoids are important components of foods (e.g., peanuts, grapes, various edible berries), beverages (wine, white tea), and medicinal plants. Many publications have described the anti-inflammatory potential of stilbenoids, including the widely known trans-resveratrol and its analogues. However, comparatively little information is available regarding the activity of their prenylated derivatives. One new prenylated stilbenoid (2) was isolated from Artocarpus altilis and characterized structurally based on 1D and 2D NMR analysis and HRMS. Three other prenylated stilbenoids were prepared synthetically (9-11). Their antiphlogistic potential was determined by testing them together with known natural prenylated stilbenoids from Macaranga siamensis and Artocarpus heterophyllus in both cell-free and cell assays. The inhibition of 5-lipoxygenase (5-LOX) was also shown by simulated molecular docking for the most active stilbenoids in order to elucidate the mode of interaction between these compounds and the enzyme. Their effects on the pro-inflammatory nuclear factor-κB (NF-κB) and the activator protein 1 (AP-1) signaling pathway were also analyzed. The THP1-XBlue-MD2-CD14 cell line was used as a model for determining their anti-inflammatory potential, and lipopolysaccharide (LPS) stimulation of Toll-like receptor 4 induced a signaling cascade leading to the activation of NF-κB/AP-1. The ability of prenylated stilbenoids to attenuate the production of pro-inflammatory cytokines tumor necrosis factor-α (TNF-α) and interleukin-1β (IL-1β) was further evaluated using LPS-stimulated THP-1 macrophages.
Keywords: signální transdukce; Signal Transduction; Humans; Transcription Factor AP-1; lipoxygenasy; stilbeny; prenylace; Prostaglandin-Endoperoxide Synthases; cyklooxygenasy; Inflammation; lidé; zánět; buněčné linie; Cell Line; Stilbenes; Prenylation; inhibitory enzymů; NF-kappa B; Lipoxygenases; transkripční faktor AP-1; Enzyme Inhibitors